2022
DOI: 10.1371/journal.pone.0263606
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of the whole mitochondrial genome identifies functionally deleterious mutations in patients with multiple sclerosis

Abstract: Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system with genetics and environmental determinants. Studies focused on the neurogenetics of MS showed that mitochondrial DNA (mtDNA) mutations that can ultimately lead to mitochondrial dysfunction, alter brain energy metabolism and cause neurodegeneration. We analyzed the whole mitochondrial genome using next-generation sequencing (NGS) from 47 Saudi individuals, 23 patients with relapsing-remitting MS and 24 healthy controls to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In certain MS lesions, ODCs were found to lack the COX‐I and COX‐IV mitochondrial subunit, an alteration potentially caused by NO and indicative of impaired oxidative phosphorylation (Mahad et al, 2008). Analysis of mitochondrial DNA also showed the presence of mutations specific to MS patients in genes encoding for functional proteins including COX‐I (Al‐Kafaji et al, 2022; Poursadegh Zonouzi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In certain MS lesions, ODCs were found to lack the COX‐I and COX‐IV mitochondrial subunit, an alteration potentially caused by NO and indicative of impaired oxidative phosphorylation (Mahad et al, 2008). Analysis of mitochondrial DNA also showed the presence of mutations specific to MS patients in genes encoding for functional proteins including COX‐I (Al‐Kafaji et al, 2022; Poursadegh Zonouzi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, MS is an etiologically unknown disease leading to neurological disabilities by demyelination in central white matter observed in young adults between the age of 20–40 [ 48 ]. Although studies continue to elucidate the causes, symptoms, and characteristics of MS, recent findings have shown that mitochondrial dysfunction plays a pivotal role in the onset and progression of MS and their related pre-clinical animal models ( Figure 1 ) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]; for revision see [ 55 ].…”
Section: Mitochondrial Dysfunction: a Hallmark In The Pathogenesis Of Msmentioning
confidence: 99%
“…Mitochondrial impairment has been associated with axonal degeneration followed by demyelination in MS [ 50 , 52 ]. An observation of post mortem MS brain tissues showed an impaired axoplasm, reduced organelle content, and fragmented neurofilaments compared with age-match healthy brain samples [ 56 ].…”
Section: Mitochondrial Dysfunction: a Hallmark In The Pathogenesis Of Msmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently sequenced the entire mitochondrial genome from unrelated native Saudi Arab individuals including patients with RRMS and healthy controls using next-generation sequencing (NGS), and identified unique and common mtDNA mutations/variants [ 32 ]. In this study, we assessed the hypothesis that mtDNA haplogroup and polymorphisms maybe an important factor in the susceptibility of MS.…”
Section: Introductionmentioning
confidence: 99%